Four components that sustain teachers' commitment to students – a relational and temporal model. Issue 5 (3rd September 2017) - Frelin, Anneli; Fransson, Göran
Abstract: Teacher commitment is a key factor for explaining how and why teachers care about their students' learning and well-being, and it is a well-known fact that teachers invest emotionally in their work and their students. The purpose of the article is to contribute to the conceptual underpinning of commitment in relation to the teacher-student relationship and to suggest a conceptual model based on empirical material. Eight teachers were selected for interview, all of whom had been in the profession since 1993 and had reported high commitment throughout their careers. The content of the teachers' accounts were analysed, with attention to how commitment to students manifested itself in their stories. The analysis resulted in a model consisting of four temporally related components of teacher commitment to students: moral, action/motivational, knowledge/self - confidence and reward/self - esteem . Understanding teacher commitment is important for preventing teacher attrition. Rather than applying general measures to boost commitment, this model provides conceptual bases for addressing deficits in particular components of teacher commitment.